INVESTIGATION OF ADIYAMAN / ZERBAN VISIT PLACE IN THE CONTEXT OF FAITH TOURISM - CONSERVATION RELATIONSHIP - Olğun, Tuba Nur; Akyildiz, Ni?Hal Arda (Ankara Haci Bayram Veli University, 2024)
Today, the tourism sector, which has diversified with increasing demand, has diversified in parallel with the increase in economic income level and transportation opportunities in many countries. It has also increased the tendency towards tourism alternatives in rural/ traditional settlement areas of individuals of different ages and cultures, who prefer to escape from the stress of daily life, especially to spend time in urban life. From this point of view, faith tourism, which has the capacity to reach the history of local religious beliefs/sects, visit important religious center symbols, and meet the expectations of individuals seeking spiritual satisfaction/pleasure as well as inner peace, has gained importance. In this context, the Alevi culture and belief, which stands out with its unique values in Anatolian culture, and the unique sacred places of this belief have also had an important place in historical, political and cultural terms. The aim of the study is to draw attention to the importance of conserving the places reflecting the Alevi tradition in all aspects as architectural heritage and cultural value. The main objectives of the study are to reveal the unique functions of the Zerban visiting place in Pınarbaşı village of Çelikhan district of Adıyaman, which draws attention with its potential to support the socio-cultural solidarity and cooperation system in Alevism, and to present its capacity in terms of faith tourism. Despite the tangible and intangible cultural heritage of the Zerban visitation site, no comprehensive study has been carried out to preserve the area with all its values. In this context, the relevant literature was examined and evaluations and inferences were made through on-site observations. As a result, suggestions are presented to protect the Zerban visit place through religious tourism and to maintain its tangible and intangible values by transferring it to future generations. © 2024 Ankara Haci Bayram Veli University. All rights reserved.
İNANÇ TURİZMİ - KORUMA İLİŞKİSİ BAĞLAMINDA ADIYAMAN / ZERBAN ZİYARET YERİNİN İNCELENMESİ
Keywords: Adıyaman; Conservation; Faith tourism; Place of faith; Zerban